Inductance gradient and current density distribution for T-shaped convex and concave rail cross-sections - Kumar, M. N. Saravana; Murugan, R.; Shivkumar, Poorani (International Journal of Engineering and Technology, 2018)
Rectangular rail was the most widely used cross section shape for the rail gun electromagnetic launching (EML) system. Based on sector assimilation, the rail gun key parameter especially current density (J) and inductance gradient (L’) greatly affected. J decides the efficiency of EML and L’ decides the force acting on the projectile of EML. So, it is mandatory to look upon the sector assimilation of rails. In this paper T shape convex and concave shape rail cross section is proposed and rail gun key design parameters are calculated by varying its dimensions using Ansoft Maxwell 2-D eddy current solver which uses finite element analysis technique to calculate these parameters. The performance of rail gun discussed using the obtained values and it has been observed and that the compared with other considered rail geometries, the T-shaped concave model shows more impact on inductance value which causes uniform current density distribution over the rails.